Peran Konseling Feminis dalam Menangani Proses Kasus Violence (Kekerasan) terhadap Perempuan - Ika Firdawati Sanger; Nurus Sa’adah; Casmini Casmini (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Violence can occur either, men or women, adults or children. However, violence occurs a lot in women, the role of counseling is present to provide strengthening of understanding related to gender construction. The purpose of the study can be seen in three formulations of the problem; first, how the role of feminist counseling. Second, forms of violence. Third; how the role of feminist counseling in the process of dealing with violence. This study uses the method of reseach library or library research methods, sources obtained through books, articles and other reliable sources. From the findings, the authors see that the role of feminist counseling has the aim of being able to remove the patriarchal system construction that is still in force with feminist consciousness, so that relationships in society provide mutual benefits, the role of feminist counseling is a role model that provides counseling assistance to individuals and communities who are experiencing problems in their lives due to misunderstanding related to gender. The forms of violence obtained are: physical violence, psychological violence, economic violence. This kind of violence can be perpetrated by women. so the role of feminist counseling is to change individuals to get out of the problem of entrenched stereotypes. So that it can maintain the right to life for him.